DESKRIPSI PENANAMAN KARAKTER PROFIL PELAJAR PANCASILA DALAM KEGIATAN P5 PADA SISWA KELAS V SEKOLAH DASAR - Meilianti, Meilianti; Kresnadi, Hery; Salimi, Asmayani; Halidjah, Siti; Pranata, Rio (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
The studi aims to describe the implementio of Pancasila profile characters in the Pancasila student profile strengthening project activities (P5) of grade V B Elementary School 82 Singkawang students. This This study is a qualitative study using a descriptive method. Data collection techniques using questionnaires, interviews, observations, and documentation. The results of the study indicate that the implementation of Pancasila student profile characters is; 1) Planning which includes the formation of a facilitator team, identifying the level of school readiness, determining dimensions, themes, and time allocation, compiling project modules. 2) Implementation of Pancasila student profile characters in P5 activities of grade VB Elementary School 82 Singkawang students is by conducting a project to make traditional drink from West Kalimantan, namely serbat water drink with the character dimensions that are desired to be brought up in students are mutual cooperation and the character dimensions of faith, devotion to God Almighty, and noble character. 3) There are supporting factors in implementation the character of Pancasila student profiles in the Pancasila student profile strengthening project activities (P5) in grade VB Elementary School 82 Singkawang students the self-concept of students, teachers/educators, environment, and family.